Work-Related Health and Burnout Patterns: A Two-Year Longitudinal Analysis of Case Managers and Administrators in Occupational Accident Insurance Services - Kurnianto, Arie Arizandi; Amer, Faten; Amiyoso, Muhammad Zaky; Zsolt, Nemeskéri; Ágoston, István (Universitas Airlangga, 2025)
Introduction: Occupational health and safety are important for professionals managing an organization’s workplace accident insurance efforts because their work influences productivity. Therefore, this study will compare the associated health and burnout related to work in case managers and administrators. Methods: A longitudinal design was adopted. This study used year-over-year surveys of 158 employee professionals with 79 case managers and 79 administrators over a two-year time frame. They measured occupational health with the questionnaires Work Ability Index (WAI) and Copenhagen Burnout Inventory (CBI). Occupational health was subsequently studied using linear regression and mixed-effects models. Results: Case managers tend to have higher work ability (mean WAI score: 45.08), but they suffer from more personal burnout (mean PB score: 33.0), presumably because they work directly with injured workers. In contrast, administrators are experiencing lower but more stable levels in their work ability (mean WAI score: 37.78) and with higher levels of client-related burnout (mean CRB score: 53.0). Further, work ability deteriorates as age increases, especially among case managers, and is negatively associated with high BMI, low sleep and long sick leave. Employees with a BMI > 30 had 12% lower WAI scores (p<0.01), and those sleeping < 6 hours per night had 15% lower work ability index. Conclusion: This study emphasizes the need for targeted interventions to alleviate occupational burnout and improve work ability, particularly through occupation-specific workplace interventions. The study also suggests that implementing stress management programs, health promotion initiatives, and workflow optimizations may improve occupational health outcomes.